Intersectional research on dementia care for people from culturally and linguistically diverse backgrounds: a protocol for a scoping review - Oliver Razum; Martina Roes; Kübra Altinok; Seda Güney; Bugse Yüceer (BMJ Open)
Introduction The specific preferences that shape the daily lives of people with dementia serve as the basis for the concept of person-centred care. However, information on the complex experiences of culturally and linguistically diverse people with dementia (CALDPwD), which determine their multifaceted preferences, is lacking. Therefore, the objective of this scoping review is to identify the range, extent and nature of evidence available in peer-reviewed and grey literature examining how the multilayered experiences of CALDPwD influence everyday living preferences.Methods We aim to conduct a scoping review to explore the multilayered experiences of CALDPwD and the intersectional determinants of their everyday living preferences. Using PubMed, MEDLINE (via Ovid for precision and controlled searching), CINAHL (via EBSCO), Scopus and the Cochrane Library, as well as grey literature, we will systematically search for literature in English, German and Turkish without any publication date restrictions. The titles/abstracts and full texts of the identified records will be independently screened by two reviewers. Data extraction will be performed by one researcher and verified by another. All the authors will discuss the conflicts. We will analyse the identified intersectional determinants of preferences using inductive content analysis.Ethics and dissemination There are no ethical concerns related to conducting this study. We will share our findings with nursing care practitioners. The results will be presented at conferences and disseminated through peer-reviewed articles and practical publications.Discussion The findings of the study will address the important gaps in knowledge on the complex intersecting factors that influence the preferences of CALDPwD. A key strength of this study is its comprehensive search strategy, which includes multiple databases and citation tracking to capture diverse, intersectional perspectives of CALDPwD. However, excluding the studies focused on caregiver’s burden may limit insights into how care systems shape the needs and expectations of this population.